From BACE1 Inhibitor to Multifunctionality of tryptoline and tryptamine triazole derivatives for alzheimer's disease - Jutamas Jiaranaikulwanitch (2018)
Efforts to discover new drugs for Alzheimer's disease emphasizing multiple targets was conducted seeking to inhibit amyloid oligomer formation and to prevent radical formation. The tryptoline and tryptamine cores of BACE1 inhibitors previously identified by virtual screening were modified in silico for additional modes of action. These core structures were readily linked to different side chains using 1,2,3-triazole rings as bridges by copper catalyzed azide-alkyne cycloaddition reactions. Three compounds among the sixteen designed compounds exerted multifunctional activities including β-secretase inhibitory action, anti-amyloid aggregation, metal chelating and antioxidant effects at micromolar levels. The neuroprotective effects of the multifunctional compounds 6h, 12c and 12h on Aβ1-42 induced neuronal cell death at 1 ?M were significantly greater than those of the potent single target compound, BACE1 inhibitor IV and were comparable to curcumin. The observed synergistic effect resulting from the reduction of the Aβ1-42 neurotoxicity cascade substantiates the validity of our multifunctional strategy in drug discovery for Alzheimer's disease. © 2012 by the authors.